Knowledge and Practice of Nurses Regarding Prevention of Deep Vein Thrombosis among Critically ill Patients Admitted in ICU In Pubic Tertiary Care Hospital: Prevention of Deep Vein Thrombosis among Critically ill Patients - Parveen, Nusrat; Masih, Sarfraz; Afzal, Muhammad (Pakistan Journal of Health Sciences, 2023)
Deep vein thrombosis is the major cause of disability and death worldwide and it is a major preventable contributor. There is a wide range of literature reported about DVT. Objective: To find out the association between education and duration of working experience of nurses with their knowledge and practice. Methods: Analytical cross-sectional study design was conducted on 56 nurses. Purposive sampling technique was used to recruiting study participants. Data were collected through international tool. Data were analyzed through SPSS VS-24. P-value ≤0.05 was considered significant. Results: Majority of the participants was females (96.4%) of mean age 33.41 ± 5.30 years and 53.6% of nurses had poor knowledge. Out of the total 56 nurses, 02(3.6%) were male and 54(96.4%) were females. Most of the nurses included in the study had a BS Nursing diploma of 23(41.1%), a general nursing diploma of 22(39.3%), and a post-basic 11(19.6%). About fifty percent (46.4%) participants had poor practices. There was a significant association between nurses’ knowledge and experience of nurses in the field (p-value<0.05). Conclusions: Nurses had good knowledge of the prevention of DVT and somehow of the practices of DVT. It was also found that, nurses have low levels of general knowledge of DVT, risk factors of deep vein thrombosis, and unsatisfactory practices about the prevention of DVT.